2016
DOI: 10.1039/c5py01687h
|View full text |Cite
|
Sign up to set email alerts
|

Study of thiol–ene chemistry on polymer brushes and application to surface patterning and protein adsorption

Abstract: The functionalisation and patterning of polymer brushes via thiol–ene chemistry is studied via ellipsometry, XPS and AFM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
63
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 54 publications
7
63
0
Order By: Relevance
“…As for the thiourethane oligomer silane, the high molecular weight and the fact that multiple alkoxy silane functionalities were available to react make it unlikely that a monolayer would be formed. In fact, prior studies demonstrated the ability of thiol-ene to bind to glass and silicone surfaces yielding polymer brush structures [36,37]. Even though the loosely crosslinked structure expected from the thiourethane is unlikely to form a polymer brush heap structure, it is reasonable to assume that the functionalization layer produced with the oligomer was thicker than the one formed with either the experimental controls.…”
Section: Discussionmentioning
confidence: 99%
“…As for the thiourethane oligomer silane, the high molecular weight and the fact that multiple alkoxy silane functionalities were available to react make it unlikely that a monolayer would be formed. In fact, prior studies demonstrated the ability of thiol-ene to bind to glass and silicone surfaces yielding polymer brush structures [36,37]. Even though the loosely crosslinked structure expected from the thiourethane is unlikely to form a polymer brush heap structure, it is reasonable to assume that the functionalization layer produced with the oligomer was thicker than the one formed with either the experimental controls.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, a method that is applicable to different types of polymer nanoarchitectures and employs reaction conditions that can be tolerated by sensitive biomolecules will allow to proceed toward more advanced functional surface structures that possess additional biological activity. Hence, the thiol–ene reaction is ideally suited in this context: it can be performed under physiological conditions and only requires mild catalysts . Besides these biocompatible reaction conditions, elaborate chemical modifications of the nanoarchitectures are not necessary, only the presence of accessible alkenes and thiol groups.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of this modularity has been demonstrated by applying stoichiometric thiol–ene and furthermore off‐stoichiometric thiol–ene (OSTE) materials for the preparation of microfluidic systems, hydrogels, microcapsules, and high internal phase emulsions . The stoichiometric imbalance between functional groups in the OSTE system results in unreacted thiol or ene groups within the polymer structure as well as on surfaces and can therefore directly be used for surface modification via TEC . Thus, hydrophilic and hydrophobic functional groups and biological moieties can easily be introduced, as well as more specific groups, such as maleic anhydride and cysteamine, which have been applied for immobilization of enzymes.…”
Section: Introductionmentioning
confidence: 99%